D2. Screening of preeclampsia (PE) in the first trimester: high total vascular resistance (TVR) with a reduced fat mass increase the risk in normo BMI patients. (12th August 2016) - Gagliardi, G.; Tiralongo, G. M.; Lo Presti, D.; Pisani, I.; Farsetti, D.; Vasapollo, B.; Novelli, G. P.; Andreoli, A.; Valensise, H.
Abstract: Introduction : Abnormalities of cardiac output, TVR and water body distribution are connected with PE and foetal growth restriction (FGR). Targets : To identify patients at risk of PE in the first trimester through USCOM system, bioimpedance and combined screening (maternal history, biophysical and biochemical markers). We enrolled 150 healthy nulliparous women with normal BMI. Results : The patients were divided into two groups: Group A (TVR <1200 dynes sec cm −5 ), Group B (TVR41200 dynes sec cm −5 ). Lower values of the Cardiac Output (CO), Cardiac index (CI), Inotropy index (INO), Heart rate (HR) and higher values of Flow Time correct (TFC) have been highlighted in the group B ( p  < 0.01) compared to group A. 8% of study population developed PE or PE + FGR. In this group 75% of the patients presented high TVR values and 50% is at high risk on the basis of combined screening. We found lower Fat Mass in complicated pregnancies with high TVR values compared to uncomplicated pregnancies with high TVR (Table 1 ). Conclusions : High TVR and lower Fat Mass in the first trimester may be an early marker of PE more than the combined screening. Moreover, lower fat mass increases the positive predictive value of isolated high TVR from 18% to 50% (Figure 1 ).